2019
DOI: 10.1089/acu.2019.1363
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention in Pregnancy and Puerperium: Acupuncture Treatment

Abstract: Background: Urinary retention (UR) during pregnancy and postpartum is a common obstetric complication. The accepted method of treatment is catheterization; this is invasive and associated with morbidity and sequelae. There are few uniform protocols for the management of this condition, and most hospitals have implemented their own guidelines. Acupuncture is a widely accepted modality of treatment in Chinese hospitals. It is quite effective and safe. It has not been well accepted globally for treating UR, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The focus is on all the symptoms that promote postoperative recovery, and no special attention has been paid to postoperative urinary retention. Two studies [ 48 , 49 ] reported a systematic review and meta-analysis of acupuncture interventions in the treatment of postpartum urinary retention. The causes of postpartum urinary retention are mostly related to the suppression of urination reflex caused by anesthetics, and reflex spasm of the bladder and posterior urethral sphincter caused by wound pain.…”
Section: Discussionmentioning
confidence: 99%
“…The focus is on all the symptoms that promote postoperative recovery, and no special attention has been paid to postoperative urinary retention. Two studies [ 48 , 49 ] reported a systematic review and meta-analysis of acupuncture interventions in the treatment of postpartum urinary retention. The causes of postpartum urinary retention are mostly related to the suppression of urination reflex caused by anesthetics, and reflex spasm of the bladder and posterior urethral sphincter caused by wound pain.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Degree III laceration above the perineal fissure; (6) Neonatal transfer after birth; (7) The investigator can terminate the subject from continuing the clinical trial at any stage, if the investigator deems that the risks of continuing the clinical trial outweigh the benefits;…”
Section: Subject Drop-out and Discontinuationmentioning
confidence: 99%
“…Traditional Chinese medicine, with its unique theory system and long-term clinical practice, has significant potential for early puerperium rehabilitation. Acupuncture and electroacupuncture have been shown to have positive significant effects in facilitating the first urination following vaginal delivery [7,8]. Hot compress, as a nonpharmacologic and noninvasive intervention, can effectively avoid the potential side effects of medications [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A distended bladder can also affect uterine contraction, increase the risk of postpartum hemorrhage, and cause maternal death. [4][5][6] Prolonged urethral catheterization or repeated catheterization within a short period can also increase the risk of urinary tract infection. [7,8] With the deepening of the traditional Chinese medicine (TCM) concept of "prevention of disease before it occurs," noninvasive TCM external treatment has shifted from treatment to prevention of PUR.…”
Section: Introductionmentioning
confidence: 99%